2019
DOI: 10.1177/0954405419868053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process combinations of milling, grinding, and polishing on the surface integrity and fatigue life of GH4169 components

Abstract: The nickel-based superalloy GH4169 is widely applied in the aviation industry due to its outstanding mechanical properties. However, many blades of GH4169 are still produced by milling and manual polishing, which is costly and unreliable. In this article, GH4169 superalloy components manufactured with combination processes of milling, grinding, and polishing were comparatively studied involving surface integrity and fatigue performance. Test results indicate that the final polishing is the most dominant proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…16 The mechanical impact can be observed at low radial engagements, through the burnishing effect, but also where lower grinding forces are found, increasing the magnitude of compressive stresses. 15,17 Work carried out by Quan et al 18 when machining GH4169 (a material similar to Inconel 718) identified compressive residual stress conditions when grinding with electroplated cBN grinding wheels to a magnitude and depth to bulk of -765 MPa and 200 mm respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The mechanical impact can be observed at low radial engagements, through the burnishing effect, but also where lower grinding forces are found, increasing the magnitude of compressive stresses. 15,17 Work carried out by Quan et al 18 when machining GH4169 (a material similar to Inconel 718) identified compressive residual stress conditions when grinding with electroplated cBN grinding wheels to a magnitude and depth to bulk of -765 MPa and 200 mm respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between surface integrity metrics and resultant component fatigue performance has been reported by several authors. 18,22 Novovic et al 22 reported that a complex relationship exists between fatigue life and workpiece microstructure, surface topography and surface integrity. However, it is generally concluded that fatigue life is benefited from compressive residual stress regimes, but that surface roughness can temper the effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly used in the manufacture of blades for aeroengines, and can significantly improve the aero-engine service life and performance. [1][2][3] However, titanium alloy has low rigidity and easily deforms. During machining, the springback of the surface is large, which can produce severe friction and lead to processing defects such as burns.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, the constant-voltage EDP is utilized due to the easier configuration, as shown in Figure 1. 21,22 Only some limited research is available in the literature concerning the EPDAP method to date. Tsui and Yan 7 studied surface polishing of stainless steel by EPDAP using silicon carbide abrasives.…”
Section: Introductionmentioning
confidence: 99%